REFLECTIONS OF A PARTICIPANT IN THE PEDAGOGICAL RESIDENCY PROGRAM, BIOLOGY IN A PANDEMIC SUBPROJECT - de Lima Victor, Luéliton; Edjane Marcelino Magalhães Escacabarossi, Francisca; Dias Pacobahyba, Lucilia (Journal of Interdisciplinary Debates, 2025)
The Pedagogical Residency program plays an important role in the teacher training of graduates, allowing students to go to schools where the program’s preceptors are located and act as teachers under the observation of these teachers. With the COVID-19 pandemic, we were impacted and surprised, having to adapt to this new reality. Faced with this, we were forced into another way of teaching through remote learning, where classes are taught online, and students and teachers use technological tools to learn and teach. At this time, we all had to reinvent ourselves and adapt in the best way we could. This report discusses the experiences of a resident in the Biology subproject during the pandemic, working at the Colégio de Aplicação of the Federal University of Roraima.